Students' Perception of the Assessment Transparency Based Google Sheet - Sri Susanti; Pratiwi Pujiastuti; Arif Wiyat Purnanto (AL-ISHLAH: Jurnal Pendidikan, 2021)
The study aims to know the students' perceptions of their Google sheet transparency assessment. The subject study was 45 students of the class 4A semester four elementary school teacher education course at the University Muhammadiyah Magelang. This research is a descriptive qualitative study, with data collection techniques is questionnaires and interviews. The Analysis techniques using Miles and Huberman's models. The results showed that students and lecture agreed on the transparency assessment of the based google sheet by complying with the nine principles of assessment: valid, objective, fair, integrated, open, comprehensive and continuous, systematic, based on criteria, and accountable. It has an impact on improving student learning outcomes. The implication of this research is to develop assessment transparency for all lecturers at University Muhammadiyah Magelang.